2013
DOI: 10.1021/ic402130p
|View full text |Cite
|
Sign up to set email alerts
|

Chloro- and Trifluoromethyl-Substituted Flanking-Ring m-Terphenyl Isocyanides: η6-Arene Binding to Zero-Valent Molybdenum Centers and Comparison to Alkyl-Substituted Derivatives

Abstract: Presented herein are synthetic and structural studies exploring the propensity of m-terphenyl isocyanide ligands to provide flanking-ring η(6)-arene interactions to zerovalent molybdenum centers. The alkyl-substituted m-terphenyl isocyanides CNAr(Mes2) and CNAr(Dipp2) (Ar(Mes2) = 2,6-(2,4,6-Me3C6H2)2C6H3; Ar(Dipp2) = 2,6-(2,6-(i-Pr)2C6H3)2C6H3) react with Mo(η(6)-napthalene)2 in a 3:1 ratio to form tris-isocyanide η(6)-arene Mo complexes, in which a flanking mesityl or 2,6-diisopropylphenyl group, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 101 publications
6
45
0
Order By: Relevance
“…But the example of the Re(III) complex also shows that the corresponding IR frequencies are sensitive to other structural features such as the trans ligand (here Cl – vs. PPh 3 ). Similar findings have been reported earlier for various complexes with m ‐terphenylisocyanides . Thus, the absolute values of these stretches should be regarded with suspicion in the discussion of the bonding situation in such compounds.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…But the example of the Re(III) complex also shows that the corresponding IR frequencies are sensitive to other structural features such as the trans ligand (here Cl – vs. PPh 3 ). Similar findings have been reported earlier for various complexes with m ‐terphenylisocyanides . Thus, the absolute values of these stretches should be regarded with suspicion in the discussion of the bonding situation in such compounds.…”
Section: Resultssupporting
confidence: 88%
“…This dual property allows isocyanides to bind well to transition metals in a range of formal oxidation states. It has been previously reported that m ‐terphenyl isocyanides can stabilize unusual low‐valent complexes of both manganese and molybdenum,, but also some medium to high valent m ‐terphenyl isocyanide complexes of Mn and Mo have been isolated via chemical oxidation of low‐valent precursors,, thereby demonstrating the utility of these encumbering ligands across a range of metal‐based redox states. Very recently, we studied reactions of m ‐terphenyl isocyanides with technetium complexes of various oxidation states and found that even technetium(V) complexes with these ligands are stabilized when strong donors such as nitrido or phenylimido ligands are present .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the past few years, we developed synthetic strategies towards new [Re( 6 -C6R6)2] + and [ 99(m) Tc( 6 -C6R6)2] + sandwich complexes. [14][15][16][17][18] Similar to other [M( 6 -C10H8)2] bis-naphthalene complexes (M = Cr, Mo), [19][20][21] coordination of the naphthalene ligands to the Re I center is comparably weak in [Re( 6…”
Section: Resultsmentioning
confidence: 90%
“…Reports of I 3 − as a terminal 6470 and bridging ligand have been described but with one metal bound η 1 to both terminal iodine atoms. 71,72 The absorption at 530 nm is attributed to a metal to ligand charge transfer band.…”
Section: Resultsmentioning
confidence: 99%